2014
DOI: 10.1111/iej.12409
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic performance by Flemish dentists: have they evolved?

Abstract: Endodontic practice of general dentists in Flanders did not always comply with quality guidelines. However, when comparing the present data with those of a previous study, an obvious trend towards a more present-day treatment protocol is noticeable, as well as an increased appeal for endodontic referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
3
23
0
4
Order By: Relevance
“…The quality of the root filling was scored inadequate in more than half (54.5%) of the root filled teeth. A recently published study by Neukermans et al (2015) reported that 56% of Flemish dentists never or seldom used rubber dam isolation during root canal treatment. Longitudinal clinical studies have shown that root canal treatment applying modern principles can yield successful outcomes with healing rates above 90% (Friedman 2002, Ng et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the root filling was scored inadequate in more than half (54.5%) of the root filled teeth. A recently published study by Neukermans et al (2015) reported that 56% of Flemish dentists never or seldom used rubber dam isolation during root canal treatment. Longitudinal clinical studies have shown that root canal treatment applying modern principles can yield successful outcomes with healing rates above 90% (Friedman 2002, Ng et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher proportion of respondents having postgraduate qualifications carried out root canal treatment using rubber dam, compared to those who did not have postgraduate qualifications [ 12 ]. Dentists with postgraduation training placed rubber dam more frequently [ 14 ], while endodontic practice of general dentists sometimes did not always comply with quality guidelines [ 4 ]. Several studies showed that rubber dam is used frequently for root canal treatment compared to operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other studies that reported the prevalence of use of magnification devices are shown in Table 2 . [ 7 13 14 15 16 17 18 19 ]…”
Section: Prevalence Of Magnification Devices Usagementioning
confidence: 99%